Northern pike : ecology, conservation, and management history - Pierce, Rodney B. (University of Minnesota Press, 2012)
The northern pike-sometimes affectionately known as the "aquatic wolf"--Is one of the most sought after and mythologized fishes in Minnesota, but until now there have been few books devoted to the history and ecological management of the species. Based on pioneering research carried out in Minnesota by leading pike specialist Rodney B. Pierce, Northern Pike Ecology, Conservation, and Management History is the most complete collection of information to date on the species, for everyone from scientists and conservation biologists to general readers and recreational anglers. A.